Detection of Diaporthe sp. in cacao plants (cv. CCN 51) in Guayas Province, Ecuador - Vera-Rodríguez, José; Villamar-Aveiga, Mónica del Rocío; Herrera-Feijoo, Robinson; Sevilla-Carrasco, Jaime; Moreno, Denny; Gavin-Moyano, Cesar; Chenche-López, Oscar (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Cacao cultivation contributes significantly to the global economy. However, a decline in production is evident due to the presence of pathogens, especially within the fungi kingdom, where some remain unidentified. The objective of this study was to identify the presence of Diaporthe sp. in cacao plants of the CCN-51 cultivar in Ecuador. Samples of cacao branches with symptoms of rot and necrotic tissue were collected (cankers). The samples were disinfected and processed in the Microbiology Laboratory of the Milagro State University, Ecuador. Cambium fragments were cultured on potato dextrose agar (PDA) and incubated at 27°C. After culture purification, morphological characterization and molecular identification were performed using ITS and EF1-α barcoding methods. The sequences were compared with the NCBI GenBank database for validation. A phylogenetic analysis was performed between the strains found and those reported in Puerto Rico and Australia. Morphological identification placed the isolates within the genus Diaporthe, which was confirmed molecularly. Phylogenetic analysis demonstrates marked genetic diversity among isolates within the genus Diaporthe. These findings suggest that Diaporthe spp. is prevalent in Ecuadorian cacao plantations and that molecular methods are effective for its identification. The presence of this pathogen implies the need for management strategies to mitigate its impact on cacao production.